2013
DOI: 10.1186/1756-8722-6-80
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant zoledronic acid therapy for patients with early stage breast cancer: an updated systematic review and meta-analysis

Abstract: BackgroundZoledronic acid is a potent inhibitor of osteoclast-mediated bone resorption and has been widely used in bone metastasis malignancies and postmenopausal osteoporosis as a preventive therapy against skeletal-related events. The purpose of this study was to evaluate the clinical outcome of zoledronic acid as an adjuvant therapy for patients with early stage breast cancer.Patients and methodsEntries in the PubMed and EMBASE databases up to 12 July 2013 were systematically reviewed. Online abstracts from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Bisphosphonates, a class of drugs commonly administered to prevent bone loss and treat osteoporosis, have been widely used to prevent disease recurrence and mortality in breast cancer metastatic patients (Hillner et al , 2003; van Poznak et al , 2011; Wong et al , 2012). Recently, a growing body of evidence is also supporting their use in women with early breast cancer to improve prognosis (Gnant et al , 2009; Coleman et al , 2013; He et al , 2013; Early Breast Cancer Trialists' Collaborative Group (EBCTCG), 2015). In addition, the use of adjuvant denosumab has been found to reduce the risk of bone fractures in postmenopausal women treated with aromatase inhibitors (Gnant et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates, a class of drugs commonly administered to prevent bone loss and treat osteoporosis, have been widely used to prevent disease recurrence and mortality in breast cancer metastatic patients (Hillner et al , 2003; van Poznak et al , 2011; Wong et al , 2012). Recently, a growing body of evidence is also supporting their use in women with early breast cancer to improve prognosis (Gnant et al , 2009; Coleman et al , 2013; He et al , 2013; Early Breast Cancer Trialists' Collaborative Group (EBCTCG), 2015). In addition, the use of adjuvant denosumab has been found to reduce the risk of bone fractures in postmenopausal women treated with aromatase inhibitors (Gnant et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Zoledronic acid (ZOL) is a third‐generation bisphosphonate, which can inhibit bone destruction in patients with metastatic bone tumors or multiple myeloma . Moreover, ZOL has been shown to exert an antitumor effect against osteosarcoma cells .…”
mentioning
confidence: 99%
“…The only two phase iii trials that considered cancer-specific primary endpoints and compared adjuvant therapy with and without za (abcsg-12 and azure) independently suggested that adjuvant za improves breast cancer outcomes in patients with low circulating estrogen levels secondary to induced or natural menopause 13,14 . Meta-analyses of adjuvant za and adjuvant bisphosphonate trials as a whole appear to confirm the benefit in that subgroup of patients 6,[15][16][17] .…”
Section: Introductionmentioning
confidence: 75%